ECHOES FROM THE SEA AND SIDE: SAN ESTEBAN’S FOLK NARRATIVES - Taer, Marvin Mariano; Villanueva, Kelvin Corbilla (Jurnal Smart, 2025)
This study examined the oral traditions of San Esteban, Ilocos Sur to uncover how folk narratives reflect cultural and social values. Addressing the lack of localized folklore research, it used qualitative methods and content analysis to interpret 17 memorates shared by cultural elders aged 50 and above. Conducted through narrative interviews in coastal barangays, stories were recorded, transcribed, and validated. Four key themes emerged: belief in supernatural beings, survival knowledge, storytelling, and spirituality. The findings affirm that these narratives are vital to cultural identity and continuity, recommending their preservation and integration into education to sustain San Esteban’s heritage.